Implementation of Halal Certification in Business Ethics for the Development of Rambak Center MSMEs in Tulungagung Regency - Yogi Dwi Lestari; Imam Mukhlis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to describe the implementation of halal certification in business ethics for the development of rambak center MSMEs in Sembung Village, Tulungagung Regency. This research is a type of qualitative descriptive research and uses purposive sampling techniques. From the research results, the implementation of halal certification in MSMEs at Rambak cracker centers is quite good. Having a halal certificate on a product shows the business actor's seriousness in complying with halal standards. The research results can detail the extent to which halal certification and support from the Department of Cooperatives and MSMEs can motivate MSMEs to develop their businesses. This research provides a comprehensive and informative picture of the relationship between the implementation of halal certification, business ethics, and the development of rambak center MSMEs in Sembung Village, Tulungagung Regency.